A REPRESENTAÇÃO DO JUDEU NO DISCURSO EUGÊNICO BRASILEIRO NO INÍCIO DO SÉCULO XX (1920-40). (Revista de História Regional, 2007)
The article proposes the study of the jews, as the representation of a discourse established in Brazil at the beginning of the 1920 is more specifically among the Brazilian intelectuals, thus have a direct influence on the life and the coming of the foreigners to the country.